KOMUNIKASI INTERPERSONAL DALAM SINETRON (Tinjauan Mengenai Romantic Relationship dalam Sinetron Si Doel Anak Sekolahan) - Yuliarti, Monika Sri (KOMUNITAS)
Soap opera is one of the the most popular products of mass media (television). âSi Doel Anak SekolahanâÂ  isÂ  oneÂ  ofÂ  theÂ  mostÂ  famousÂ  IndonesiaÂ  soap opera.Â  Meanwhile,Â  oneÂ  ofÂ  theÂ  mass mediaÂ  functionÂ  isÂ  socialization/Â  transmissionÂ  ofÂ  socialÂ  valuesÂ  function,Â  inÂ  whichÂ  theÂ  mass media display the values held by certain people inÂ  itâs program, which later, audiences will adopt them into their daily lives. Romantic relationship is one the relationship that is created from the process of interpersonal communication between people. On the other hand, soap opera consists of many values of the romantic relationship. This study findings are: there are 4Â  valuesÂ  ofÂ  romanticÂ  relationshipÂ  whichÂ  isÂ  shownÂ  in thisÂ  soapÂ  opera,Â  whichÂ  isÂ  love, commitment, passion constructive, and intimacy. Those values tend to embodied in non verbal language,Â  andÂ  theÂ  trendÂ  isÂ  stillÂ  withinÂ  inÂ  theÂ  limitsÂ  basedÂ  onÂ  eastÂ  cultureÂ  ofÂ  Indonesia. Meanwhile, from three main characters involved in alove triangle story, a character who is described tends to apply romantic relationship values is Zaenab. Keywords: romantic relationship, si Doel, sinetron,interpersonal communication